Monetary and Financial Cooperation in East Asia: The Chiang Mai Initiative and Beyond - Pradumna B. Rana (Asian Development Bank (ADB), 2002)
"Until recently, not much attention had been paid to the need to promote regional monetary and financial cooperation. This is surprising as cooperation in finance provides more opportunities for "win-win" situations. However, the pace of monetary and financial cooperation has picked up in the postcrisis period. Countries in East Asia appear to have mustered a certain amount of "political will" to propel the process further. Cooperation has ranged from information exchange and surveillance, to establishing regional financing facilities and early warning systems. Beyond the Chiang Mai Initiative, efforts are also under way to coordinate macroeconomic and exchange rate policies mainly under the ASEAN Task Force on ASEAN Currency and Exchange Rate Mechanism of the AsiaEurope Finance Ministers group. As a regional development bank, the Asian Development Bank is supporting the efforts of its developing member countries to strengthen regional monetary and financial cooperation."
hdl:11540/1921
Keywords: 330